Prevalence of HBV and HCV Infections and Associated Risk Factors in Addict Prisoners - AA Javadi; M Avijgan; M Hafizi (Tehran University of Medical Sciences, 2006)
High prevalence of HBV and HCV infections in prisoners suggests them as one of the main infection source in community. Preventive measures can possibly decrease their rate of infection and infectivity. We evaluated prevalence of HBV and HCV infections and their relation to dangerous behavior in addict prisoners. This was a cross-sectional study included prisoners of central provinces of Iran who were evaluated for HBV and HCV in 2003. All of 1431 prisoners filled out questionnaires that were evaluated for HBsAg and HCV antibody. There were 51 prisoners (3.5%) who were HBsAg positive and 513 prisoners (35.8%) had HCV antibody. Odd`s ratio for HBV and HCV were 10.3 and 9.6 for IVDA, respectively. This study showed that the HBV and specially HCV infection had high prevalence among prisoners. In comparison to rate of HBsAg and HCV infection in general population of Iran, this study showed that the HBsAg was 2 times and HCV infection was 70 times more frequent in prisoner than in general population of Iran. The education for dangerous behavior is strongly recommended to control this persistent infection source for hepatitis B and C in the community.